PENINGKATKAN KEMAMPUAN GURU MATEMATIKA DALAM MELAKSANAKAN PENELITIAN TINDAKAN KELAS MELALUI BIMBINGAN INDIVIDUAL DI SMP NEGERI 3 KOTA BIMA - Arnasari Merdekawati Hadi; Saifullah Saifullah (SUPERMAT : Jurnal Pendidikan Matematika, 2018)
In an effort to develop teacher competencies according to ongoing needs to improve the profession according to their duties, the first teacher with the rank of Young Administrator up to the main teacher with the position of Main Trustee must carry out continuous professional development namely 1) self-development, 2) scientific publications, 3) development of innovative work, this is based on the Regulation of the Minister of State for Bureaucratic Reform 16 of 2009. The reality in the field shows that there are still many mathematics teachers in SMP Negeri 3 Kota Bima who need to be fostered in this matter. Some teachers still do not understand how to make proposals, carry out and report the results of their research well, and some others who have understood but have not implemented it. This tends to be due to the attention of teachers to conduct research and write scientific papers is still very low. This study aims to improve the ability of mathematics teachers at SMP Negeri 3 Kota Bima to carry out classroom action research through individual guidance techniques. The type of research used is class action research (PTK) which is carried out in the Middle School 3 of Bima City in the even semester of the 2017/2018 school year starting from January 2018 to March 2018. The research subjects were five mathematics teachers. The instruments used in this study were teacher observation sheets and interview sheets. The results showed that there was an increase in the ability of teachers to carry out classroom action research. This can be seen from the increase in teacher performance results from the first cycle of 2,36 with a fairly good category to 3,38 in the good category in the second cycle.